Highly Efficient 2D NIR-II Photothermal Agent with Fenton Catalytic Activity for Cancer Synergistic Photothermal–Chemodynamic Therapy - Zhang, Q. (John Wiley and Sons Inc., 2021)
10.1002/advs.201902576